Exploring Data Mining Applications and Techniques: A Comprehensive Research Survey - Vasumathy , M.; Agarwal , Ujjwal; Divyamrutha , G.; Pallathadka , Harikumar; Manoharmayum , Dolpriya Devi (International Journal of Membrane Science and Technology, 2023)
Every second, huge amount of data is generated and accumulated. This data could possibly be used in forecasting the future. Data mining uses this data and generates valuable information which can be transformed into relevant knowledge. Data mining is a technique of identifying outliers, behaviours, trends of patterns and relationship among huge datasets. It is hugely associated with the skill of decision making. The knowledge on a relevant subject will help in understanding future trends. This survey paper supplies the overview of data mining, the processes involved, the scope it can offer, its different techniques and multiple applications. Data mining is a great model of using data efficiently.